Analisis Pengaruh Current Ratio, Firm Size Dan Free Cash Flow Terhadap Dividend Payout Ratio Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2012-2015 - Ana, Amalia Nur Fitri; , Imron Rosyadi S.E., M.Si (2017)
This study aims to test the effect of the current ratio, firm size, and free cash flow dividend payout ratio at manufacturing companies in the Indonesia Stock Exchange. The population of the study are go public manufacturing companies in Indonesia Stock Exchange. Samples were the form of financial statements during the period 2012 to 2015 as many as 16 companies. Sample selection is done by purposive sampling method. The data were the publication of financial statements by the Indonesian Stock Exchange gained through www.idx.com site. The result of t test analysis that the variable firm size and free cash flow do not have any impact on the dividend payout ratio. Variable current ratio has an influence on the dividend payout ratio and the F test analysis results obtained F count> F table and a p-value <p-α (4.318> 2.62 and 0.012 <0.05), then Ho is rejected. This means that the variable current ratio, firm size, and free cash flow together jointly influenced the dividend payout ratio. The results of test analysis coefficient of determination (R^2) is known Adjusted R square of 0.237. it shown that the variation of the dividend payout ratio can be explained by the variable current ratio, firm size, and free cash flow by 23.7%, while the rest explained 76.3% influenced by other factors beyond the variables has been studied.